Fingerprint Protected Password Authentication Protocol. (26th June 2019) - Yang, Chao; Zhang, Junwei; Guo, Jingjing; Zheng, Yu; Yang, Li; Ma, Jianfeng
Abstract : With the rapid development of industrial Internet of things (IIOT), a variety of cloud services have been deployed to store and process the big data of IIOT. The traditional password only authentication is unable to meet the needs of security situation in IIOT. Therefore, a lot of mobile phone assisted password authentication schemes have been proposed. However, in existing schemes, the secret information is required to be stored in the user's mobile phone. Once the phone is lost, the secret information may be obtained by the opponent, which will bring irreparable loss to the user. To address the above problems, we propose a fingerprint protected password authentication scheme which has no need to store the secret parameter in the mobile phone. When a user logs in, he uses his mobile phone to generate the private key which is used to decrypt the encrypted text generated during the registration phase. The process of generating the private key needs to enter the password and the fingerprint. When the computer interacts with the mobile phone, the user's password will be blinded so that it can protect the user's password from adversary's attacks. Theoretical analysis and experimental results show that our scheme improves the security of the user's secret. Meanwhile, our scheme can resist the opponent's dictionary attacks, replay attacks, and phishing attack. Our scheme can reduce the storage pressure of the mobile phone and is easy to deploy.